The Effect of Painting-Based Art Therapy on Aggressive Behavior of Female Students with Hearing Impairment - Rahimi pordanjani , Saeed; Jalali , Darioush; Nejatifar, Sara; Arabi , Elaheh (Journal of Assessment and Research in Applied Counseling (JARAC), 2021)
Background and Aim: Adaptation problems in children with hearing impairment require therapeutic interventions. Therefore, this study was conducted to investigate the effect of painting-based art therapy on the aggressive behavior of female students with hearing impairment. Methods: This was a quasi-experimental study with a pretest-posttest design, control and experimental groups, and a three-month follow-up. The statistical population included female students with hearing impairment who were studying in special schools of Shahrekord in the academic year 2019-2020, from which 30 students who met the inclusion criteria were selected by the convenient sampling method and assigned to the experimental group (n = 15) and the control group (n = 15) after matching. The experimental group received a painting therapy package for 15 sessions, and the control group received no intervention. All subjects were assessed in the pre-test and post-test stages by Buss and Perry's (1992) Aggression Questionnaire. Data were analyzed using repeated-measures ANOVA and SPSS 24 software. Results: The results indicated that painting-based art therapy reduced aggressive behavior and the components of anger, verbal aggression, and resentment both in the post-test and follow-up stages (P